Elasmobranch Conservation in India: Assessing Threats and Strategies for Sustainable Management - Makwana, Ketan; Parmar, H. L.; Ragul, Sivakumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Elasmobranchs, a group that includes sharks, rays, and skates, play a crucial role in marine ecosystems as apex predators and benthic regulators. However, they face significant threats that jeopardize their populations and overall biodiversity. Major threats include overfishing, bycatch, habitat degradation, pollution, and climate change. Overfishing, driven by high demand for shark fins and ray gills, alongside unregulated fishing practices, has led to drastic declines in many species. Bycatch in commercial fisheries further exacerbates their vulnerability. Additionally, habitat destruction due to coastal development and pollution impacts their breeding and feeding grounds. Climate change contributes to shifts in ocean temperature and acidity, affecting elasmobranch physiology and distribution. Effective conservation strategies are essential to address these threats and ensure the sustainability of elasmobranch populations. Key measures include implementing and enforcing sustainable fishing practices, creating marine protected areas, reducing bycatch through improved fishing gear, and enhancing global cooperation for conservation efforts. Addressing these threats requires a multifaceted approach involving scientists, policymakers, and local communities to safeguard the future of elasmobranch species and maintain the health of marine ecosystems.